Introducing Critical Theoy : A complete Guide - Stuart Sim (Introducing (Thriplow, England), 2009)
The last few decades have seen an explosion in the production of critical theories, with deconstructionists, poststructuralists, postmodernists, second-wave feminists, new historicists, cultural materialists, postcolonialists, black critics and queer theorists, among a host of others, all vying for our attention. The world around us can look very different on the critical theory applied to it. This vast range of interpretations can leave one feeling confused and frustrated. This book provides a route through the tangled jungle of competing theories.